PRODUCTION LEAD TIME VARIABILITY SIMULATION – INSIGHTS FROM A CASE STUDY - Finke, Gandolf R.; Singh, Mahender; Schönsleben, Paul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
We study the impact of disruptions to operations that can cause deviations in the individual processing time of a task, resulting in longer than planned production lead time. Quality, availability of capacity and required material as well as variability in process times are regarded as drivers of disruption. The focus is to study the impact of variability in the lead time on the overall performance of the production system, instead of the average lead time. Structural and numerical application of the approach are provided in a case study. Additionally, the different dimensions of practical implications of this research are accentuated. Accordingly, discrete event simulation is used to study the interactions and draw insights based on a case study. Measures to mitigate lead time variability are discussed and their impact is analyzed quantitatively.